Thinking with Foucault: a reading for experienced analysts (Acta Scientiarum. Language and Culture, 2014)
FISCHER, Rosa Maria Bueno. Trabalhar com Foucault: arqueologia de uma paixão. Belo Horizonte: Autêntica, 2012. 167 p. ISBN 978-85-65381-00-0